Comparison of suction catheter versus forceps biopsy for sampling of solitary pulmonary nodules guided by electromagnetic navigational bronchoscopy - Eberhardt, Ralf; Morgan, Ross K.; Ernst, Armin; Beyer, Thomas; Herth, Felix (Respiration, 2010)
Background: Electromagnetic navigation has been approved for use as an adjunct to standard bronchoscopy. The diagnostic yield varies depending on the size of the lesion and successful navigation to the lesion. Objectives: The performance of two different biopsy tools, i.e. catheter aspiration and forceps biopsy, in the diagnosis of small pulmonary nodules (SPN) guided by electromagnetic navigational bronchoscopy (ENB) was examined. Methods: 54 patients referred for suspected lung cancer underwent ENB and 55 SPN (<3 cm) were sampled using both techniques. Endobronchial ultrasound (EBUS) was used to verify the accuracy of target lesion localization by ENB. Primary end points of the study were successful navigation to the lesion and a positive diagnosis. Patients were followed until a definitive diagnosis was obtained. Results: All 55 lesions were accessed. Two lesions were excluded from data analysis as the patients were lost to follow-up and their diagnoses could not be confirmed. Of the remaining 53 lesions, 40 samples (75.5%) were diagnostic. Compared to forceps biopsy, catheter aspiration was positively correlated with the success rate (36/40 vs. 22/40; p = 0.035). The diagnostic yield was 93% when EBUS verified the lesion location after navigation and only 48% when lesion location was not confirmed. There were no significant complications. Conclusions: ENB is a useful tool in the evaluation of SPN <3 cm in diameter. For malignant lesions, sampling by catheter aspiration is associated with a higher diagnostic yield than sampling by forceps biopsy alone, in particular when EBUS could not confirm lesion location prior to sampling.